A Novel Absolute Sine-Carrier PWM-Based Discontinuous Space Vector Modulation for Vienna Delta-Switch Rectifiers with Comparative Performance Evaluation - Kanyarat Ek-iam; Prapawan Pangsri; Ong-ard Tubburee (International Journal of Engineering and Technology Innovation, 2026)
This paper proposes an absolute sine-carrier pulse-width modulation (ASC-PWM) integrated with a discontinuous space-vector modulation (DSVM) framework for Vienna delta-switch rectifiers, aiming to improve input-current quality and harmonic performance while maintaining simplicity of implementation. The absolute sinusoidal carrier reshapes the pulse distribution while preserving the simplicity of comparator-based PWM. Closed-form dwell-time expressions and sector-dependent switching-state remapping are derived under unidirectional current-flow constraints. A voltage-oriented control (VOC) scheme is employed for DC-link regulation and power factor correction. Simulation results for a 230-V/50-Hz grid-connected system at 2.5 kHz demonstrate that the proposed method achieves lower total harmonic distortion of the input current and a higher power factor than the triangular, symmetrical sine, and inverted sine carriers. Although the proposed strategy yields a lower DC-link voltage due to reduced duty cycle, it provides superior harmonic performance with stable voltage regulation, making it suitable for high-power grid-connected rectifiers that prioritize input power quality.